Does typing of Chlamydia trachomatis using housekeeping multilocus sequence typing reveal different sexual networks among heterosexuals and men who have sex with men?. Issue 1 (December 2016) - Versteeg, Bart; Bruisten, Sylvia; van der Ende, Arie; Pannekoek, Yvonne
Abstract Background Chlamydia trachomatis infections remain the most common bacterial sexually transmitted infection worldwide. To gain more insight into the epidemiology and transmission ofC. trachomatis, several schemes of multilocus sequence typing (MLST) have been developed. We investigated the clustering ofC. trachomatis strains derived from men who have sex with men (MSM) and heterosexuals using the MLST scheme based on 7 housekeeping genes (MLST-7) adapted for clinical specimens and a high-resolution MLST scheme based on 6 polymorphic genes, includingompA (hr-MLST-6). Methods Specimens from 100C. trachomatis infected men who have sex with men (MSM) and 100 heterosexual women were randomly selected from previous studies and sequenced. We adapted the MLST-7 scheme to a nested assay to be suitable for direct typing of clinical specimens. All selected specimens were typed using both the adapted MLST-7 scheme and the hr-MLST-6 scheme. Clustering ofC. trachomatis strains derived from MSM and heterosexuals was assessed using minimum spanning tree analysis. Results Sufficient chlamydial DNA was present in 188 of the 200 (94 %) selected samples. Using the adapted MLST-7 scheme, full MLST profiles were obtained for 187 of 188 tested specimens resulting in a high success rate of 99.5 %. Of these 187 specimens, 91 (48.7 %) were from MSM and 96 (51.3 %) from heterosexuals. We detected 21 sequence types (STs) using the adapted MLST-7 and 79 STs using the hr-MLST-6 scheme. Minimum spanning tree analyses was used to examine the clustering of MLST-7 data, which showed no reflection of separate transmission in MSM and heterosexual hosts. Moreover, typing using the hr-MLST-6 scheme identified genetically related clusters within each of clusters that were identified by using the MLST-7 scheme. Conclusion No distinct transmission ofC. trachomatis could be observed in MSM and heterosexuals using the adapted MLST-7 scheme in contrast to using the hr-MLST-6. In addition, we compared clustering of both MLST schemes and demonstrated that typing using the hr-MLST-6 scheme is able to identify genetically related clusters ofC. trachomatis strains within each of the clusters that were identified by using the MLST-7 scheme.